DNA methylation profiling in acute myeloid leukemia: from recent technological advances to biological and clinical insights. (September 2010) - Claus, Rainer; Plass, Christoph; Armstrong, Scott A; Bullinger, Lars
Acute myeloid leukemia represents a heterogeneous malignant hematological disease with a complex underlying biology suggesting multiple patterns of genetic and epigenetic alterations. Recent evidence suggests that epigenetic mechanisms, especially deregulation of DNA methylation, play an important pathogenic role in leukemogenesis and the first epigenetic drugs have entered the clinic. Therefore, an improved understanding of the impact of altered epigenetic patterns on leukemogenesis represents a pre-requisite for improved patient management and outcome. Here, we provide an overview of current advances in deciphering the leukemic epigenome and its clinical relevance. Recent high-throughput analyses and genome-wide studies provide an optimal starting point for future epigenetic and integrative analyses that will further the development and use of predictive and prognostic epigenetic markers in acute myeloid leukemia.